DISPENSATIONS MARRIAGE THROUGH THE APOSTOLIC DATARIA. FUNCTIONS AND PROBLEMS IN THE XVIII AND XIX CENTURIES. - Henarejos López, Juan Francisco (Revista de Historia Social y de las Mentalidades, 2017)
This paper focuses on the study of the  Roman Apostolic Dataria and its influence  on the processing and granting of marriage  dispensations in Spain. Although various  contributions made by the international  historiography, there are still many unresolved  issues. The diverse matrimonial law and its  evolution will be marked by the performance  of this Roman institution at various times,  especially in the eighteenth and nineteenth  centuries. Our goal is to provide response to  an institution of great importance in obtaining  and validation of marriage dispensations. A the same time, investigate the conflict generated  in this institution during the Old Regime. For  it have been used different documents from the  Vatican Secret Archives and Archives and Spanish  libraries
Keywords: Dataria Apostolic; Dispensations; External forum; Marriage; Rome